(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was conducted to isolate and diagnose the most important bacterial types causing urinary tract infection from the inpatients and outpatients to Salah El Din General Hospital using routine isolation and diagnosis methods. 70 samples were isolated, and the results showed two types of growth: Gram positive bacteria and Gram negative bacteria, where 10 bacterial types were isolated as follows: E. coli 42.85%, Kleibsiella. pneumonia 21.42% roteus mirabilis (11.42%), Staphylococcus aureus (7.14%), Enterobacter cloaca (5.71%), Serratia marcescens (2.85%), Pseudomonas aeruginosa (2.85%), Staphylococcus Saprophyticus. 2.85%, Micrococcus luteus 1.42%, and Citrobacter freundii 1.42%. The results of the susceptibility test for 9 types of antibiotics using the discs method showed a change in the level of resistance to different antibiotics. The most effective antibiotics were Imipenem, Ciprofloxacin and Sulfamethoxaole. Plant extracts (both aqueous and alcoholic) of Sambucus nigra and Tribulus terrestris fruits were used, and tested for their ability to inhibit the most isolated bacteria (E. coli , K. pneumonia P. mirabilis and S. aureus ). All alcoholic extracts were effective in the direction of Bacterial isolates, while aqueous extracts, have little or no effect.